Comparison of Audiometric and Functional Outcomes Between the Standard and Modified 360 Nitinol Shape Memory Stapes Prostheses. Issue 8 (September 2015) - Lavy, Jeremy; Huins, Charlie; Khalil, Sherif; Hall, Andrew; Hughes, Owain
Abstract : Objective: To compare audiometric and functional outcomes between two designs of heat-activated self-crimping stapes prostheses—a modified shape memory circumferential nitinol-Teflon piston versus its predecessor—in patients with otosclerosis. Study Design: A retrospective analysis of preoperative and postoperative hearing thresholds. Setting: Tertiary referral center and teaching hospital. Patients: One hundred sixty-three consecutive procedures of primary stapes surgery for clinically proven otosclerosis in 108 women and 55 men with an average age of 46 years. Intervention: Stapedotomy and insertion of either a standard or a circumferential stapes prosthesis. Main Outcome Measures: Four-frequency pure-tone average preoperative and postoperative air-bone thresholds were recorded. A secondary outcome measure was stability of the implant, as measured by failure rates. Results: Success of closure of the air-bone gap to within 10 dB was achieved in 97% and comparable in both groups (original prosthesis, 23.6; standard deviation, 7.3, with the average reduction seen in the circumferential prosthesis group being 22.6, standard deviation, 5.6). All the differences were not statistically significant using two-way analysis of variance. Failure rate for the original piston was 6%, with no failures seen with the circumferential piston. Conclusion: Both prostheses showed comparable postoperative hearing outcomes, with the circumferential prosthesis being found to be more stable.